2023
DOI: 10.1002/mds.29595
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Disinhibition Drives Freezing of Gait in Parkinson's Disease and an Exploratory Repetitive Transcranial Magnetic Stimulation Study

Huimin Sun,
Caiting Gan,
Lina Wang
et al.

Abstract: BackgroundDysfunction of the primary motor cortex, participating in regulation of posture and gait, is implicated in freezing of gait (FOG) in Parkinson's disease (PD).ObjectiveThe aim was to reveal the mechanisms of “OFF‐period” FOG (OFF‐FOG) and “levodopa‐unresponsive” FOG (ONOFF‐FOG) in PD.MethodsWe measured the transcranial magnetic stimulation (TMS) indicators and gait parameters in 21 healthy controls (HCs), 15 PD patients with ONOFF‐FOG, 15 PD patients with OFF‐FOG, and 15 PD patients without FOG (Non‐F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…1 Still, motor cortex disinhibition is highly variable across patients, and the origin and significance of this variability remain unclear. As a possible solution for the variability puzzle, a recent study suggested that motor cortex disinhibition of the hand area in PD may be specifically associated with freezing of gait (FOG), 6 which becomes particularly prevalent in advanced stages of PD. But the association is at odds with the fact that motor cortex disinhibition does not seem to progress in advanced compared to early stages of PD.…”
Section: Motor Cortex Disinhibition Is Not Associated With Freezing O...mentioning
confidence: 99%
“…1 Still, motor cortex disinhibition is highly variable across patients, and the origin and significance of this variability remain unclear. As a possible solution for the variability puzzle, a recent study suggested that motor cortex disinhibition of the hand area in PD may be specifically associated with freezing of gait (FOG), 6 which becomes particularly prevalent in advanced stages of PD. But the association is at odds with the fact that motor cortex disinhibition does not seem to progress in advanced compared to early stages of PD.…”
Section: Motor Cortex Disinhibition Is Not Associated With Freezing O...mentioning
confidence: 99%
“…In addition to various physiological processes, disinhibition has been proposed as a pathophysiological substrate of various diseases. In Parkinson's disease, disinhibition in the primary motor cortex has been suggested as one of the first manifestations [70] and is correlated with freezing and gait impairment [71]. Obesity is associated with disinhibition of the orbitofrontal cortex.…”
Section: Disinhibitionmentioning
confidence: 99%